Vigilância e controlo do trabalho dos mesteirais através da fiscalidade paroquial: o caso de Coimbra no século XIV - Campos, Maria Amélia Álvaro de (2021)
Among the several powers that governed the medieval Portuguese city, this study will focus on Church – the institution that closely observed people’s life in spiritual, material, and moral aspects, as well as in leisure and work. This article starts by characterizing the parochial insertion of the craftsmen of Coimbra, and then it will focus on the following main question: what can we know about crafts activities in Coimbra by analysing the administration of parochial taxation? To answer that, we propose a study case based on the examination of judicial sentences produced by the episcopal audience to solve processes on the collection of ecclesiastical tithes of the crafts activities, during the 14th century. From this study, we want to understand who the craftsmen of Coimbra were, which problems they found in its relationship with ecclesiastical powers, and how they organised their work. Furthermore, we will reflect on its parochial insertion and perceive how it conditioned the production and the income of crafts activities.